Conservation agriculture in rice and maize based cropping systems for enhancing crop and water productivity: participatory technology demonstration in north-east India (Indian Journal of Soil Conservation, 2026)
Conservation Agriculture (CA) in rice (Oryza sativa L.) and maize (Zea mays L.) based cropping systems for crop diversification and higher productivity was demonstrated in a participatory mode in 15 farmers' field covering 10 villages across Ri-Bhoi District, Meghalaya during 2010-12. The results indicated significant improvement in cropping intensity, crop and water productivity, employment and income due to adoption of CA approach compared to the Farmers' Practice (FP) of monocropping under conventional tillage. Minimum tillage was followed for kharif crops and no-till was practiced for dry season crops. French bean and rapeseed was grown after maize and pea and lentil was grown after lowland rice with conserved moisture resulting in doubling of cropping intensity. The productivity enhancement in terms of Rice Equivalent Yield (REY) with rice-pea sequence under CA was 229% compared to FP of rice monocropping. Similarly, maize-French bean under CA recorded 168% higher maize equivalent yield (MEY) compared to monocropping of maize. The maximum enhancement in net return was observed with maize-French bean (465%) followed by rice-pea (360%) under CA over respective FP. Adoption of CA resulted substantial improvement in employment of farmers. Adoption of CA enhanced water use efficiency (WUE) by 12% with maize-rapeseed sequence to as high as 228% under rice-pea sequence. Maximum WUE was achieved with rice-pea system under CA (19.69 kg ha mm) followed by rice-lentil sequence (12.34 kgha mm) compared to 5.99 kg ha mm under monocropping of rice and 6.23 kg ha mm under monocropping of maize under FP. The water productivity of rice- pea (9.57 m water) and maize-French bean (6.59 m water) sequences were almost four times higher compared to that under FP of monocropping rice ( 2.66m water) and maize (1.80m water). Thus, the study indicated opportunity of CA in north eastern hill region for conserving natural resources and enhancing productivity.